PENGARUH PROMOSI MEDIA SOSIAL TIKTOK TERHADAP MINAT BELI KONSUMEN PRODUK SKINCARE SKINTIFIC DENGAN BRAND TRUST SEBAGAI VARIABEL INTERVENING PADA GENERASI Z DI KOTA MALANG - Cahyo Nugroho, Dodit; Sadiqin, Amin (Penerbit Lafadz Jaya, 2026)
This study examines the influence of TikTok social media promotion on consumer purchase intention toward Skintific skincare products, with brand trust positioned as an intervening variable among Generation Z consumers in Malang City. The study is grounded in social media marketing, brand trust, and consumer behavior perspectives, emphasizing how short-video promotional exposure, interactive content, creator credibility, entertainment value, and algorithmic visibility may shape trust and intention in digital skincare consumption. The proposed research uses an explanatory quantitative design with purposive sampling. The target respondents are Generation Z consumers aged 18-29 years who live, study, or work in Malang City, use TikTok, and have been exposed to Skintific promotional content. Data are proposed to be collected through a structured Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The illustrative analysis suggests that TikTok promotion positively affects brand trust and purchase intention, while brand trust positively affects purchase intention and partially mediates the effect of TikTok promotion on purchase intention. The novelty of this article lies in its integration of TikTok-specific promotional mechanisms, brand trust mediation, Skintific as an international skincare brand strongly circulated in Indonesian digital commerce, and Malang City as an education-oriented urban market with a dense Generation Z population. The findings are expected to contribute to digital marketing theory and provide managerial implications for skincare brands seeking to convert TikTok engagement into trust-based purchase intention.